(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2002)
A set of natural numbers is generic relatively a set B if and only if it is the preimage of some set A using a B-generic B-regular enumeration such that both A and its complement are e-reducible to B.